METODE PELAKSANAAN PEKERJAAN SHEAR WALL PADA PROYEK PEMBANGUNAN APARTEMEN SILK TOWN ALEXANDRIA TOWER - Nurdiana, Iyan; Kholiq, Abdul (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The Silk Town Alexandria Tower apartment project is one of the apartment projects in the city to meet the needs of the megapolitan community for residential homes. This apartment is a people's dream to have a modern residence with luxurious facilities. This project has a very strategic location, namely in the Graha Raya area. South Tangerang, precisely on Jalan Bhayangkara, Alam Sutra. Tangerang Selatan is a location that is experiencing rapid development. In addition, South Tangerang, which is close to the capital city, makes this location in great demand and targeted by the community. Shear walls are vertical elements of the horizontal force resisting system. Shear walls are like vertically-oriented wide beams that carry earthquake loads downwards to the foundation. Shear walls are efficient, both in terms of construction cost and effectiveness in minimizing earthquake damage in structural and nonstructural elements. Shear walls in buildings must be symmetrically located in plan to reduce ill-effects of twist in buildings. The presence shear wall building is expected to reduce the earthquake plan so that the safety and comfort of residents under control.